Inhalational Isoflurane Sedation in Patients with Decompressive Craniectomy Suffering from Severe Subarachnoid Hemorrhage: A Case Series - Lehmann, Felix; Müller, Marcus; Zimmermann, Julian; Güresir, Ági; Lehmann, Victoria; Putensen, Christian; Vatter, Hartmut; Güresir, Erdem (Journal of Neuroanaesthesiology and Critical Care, 2019)
Background Severe aneurysmal subarachnoid hemorrhage (SAH) may lead to the necessity of decompressive craniectomy (DC) to treat refractory elevated intracranial pressure (ICP). In some patients, adequate deep sedation, as one part of conservative treatment, cannot be achieved. Recent investigations suggest that inhalative sedation might not be as detrimental as considered before, and therefore a treatment option.Materials and Methods A retrospective analysis of seven patients was performed who suffered from aneurysmal SAH (Hunt-Hess grade 3–5, Fisher's score 3) and underwent DC due to a critically elevated ICP. In these patients, the target sedation level could not be achieved even with high doses of intravenous sedatives. Thus, the sedative regimen was switched to inhaled anesthesia with isoflurane. Mean arterial pressure (MAP), ICP, cerebral perfusion pressure (CPP), levels of vasopressors, and respiratory parameters were analyzed.Results Deep sedation (Richmond Agitation-Sedation Scale [RASS] −5, mean–fractional end-expiratory gas concentration [mean-Fet] 0.78%) was rapidly achieved in all patients after commencing general anesthesia with isoflurane. ICP remained stable when comparing 1 hour before the onset of isoflurane sedation (1) with 6 (2), and 12 hours (3) after commencing isoflurane anesthesia (mean ICP [1] 13.83 mm Hg; [2] 12.57 mm Hg; [3] 11.14 mm Hg). The mean duration of application was 9 (± 4) days. CPP could be maintained above 70 mm Hg without the need for extended vasopressor usage.Conclusion In a setting of severe SAH and critically elevated ICP with the need for aggressive multimodal therapy, isoflurane was safely applied in those patients. Our sedation goal was rapidly achieved and critical rise in ICP was not observed. Further investigations are required to demonstrate that inhaled anesthesia with isoflurane can be a promising alternative option, as this drug has better controllable pharmacokinetics, no clinically relevant accumulation of the drug itself, and potential neuroprotective effects (so far reported in different animal models).
Keywords: decompressive craniectomy; intracranial pressure; sedation; subarachnoid hemorrhage; volatile anesthetics